PENGARUH KOMPETENSI, PENGENDALIAN INTERNAL, KUALITAS INFORMASI AKUNTANSI, DAN KOMITMEN ORGANISASI PADA KINERJA PERUSAHAAN (STUDI PADA PT BINA ARTHA VENTURA KAB.KEBUMEN) - Dimas Kusuma Wardana (JURNAL EKOBIS DEWANTARA, 2018)
Abstract The purpose of this study was to determine (1) joint influence between competence, internal control, quality of accounting information, and organizational commitment to company performance in PT. Bina Artha Ventura Kebumen branch, (2) the influence of competence on company performance in PT. Bina Artha Ventura Kebumen branch, (3) the influence of internal control on company performance in PT. Bina Artha Ventura Kebumen branch, (4) influence the quality of accounting information on the performance of the company in PT. Bina Artha Ventura Kebumen branch, and (5) the influence of organizational commitment to company performance in PT. Bina Artha Ventura Kebumen branch. This research is Ex Post Facto research. Population in this research is all employees at PT. Bina Artha Ventura Kebumen branch consisting of 3 branches as many as 36 employees. The sampling technique used purposive sampling technique. The sample in this research were employees at PT. Bina Artha Ventura Kebumen branch of administration and finance as much as 32 employees. Data collection techniques used questionnaires. The results showed that (1) there was a mutual influence between competence, internal control, quality of accounting information, and organizational commitment to company performance in PT. Bina Artha Ventura Kebumen branch. It is shown from value equal to 26,770 bigger than value equal to 2,728 at significance level 5%, value of regression coefficient equal to 0,894 positive value, with value signifikansi 0,000 <0,05; (2) there is influence between competence to company performance at PT. Bina Artha Ventura Kebumen branch. This is shown from the value of tcount is greater than ttable value (3,806> 2,042), significance value 0,000 <0,05, and regression coefficient have positive value equal to 0,235, (3) there is influence of internal control to company performance at PT. Bina Artha Ventura Kebumen branch. This is shown from the value of tcount is greater than ttable value (3,329> 2,042), significance value 0,003 <0,05, and regression coefficient have positive value equal to 0,465; (4) there is influence of accounting quality of information to company performance at PT. Bina Artha Ventura Kebumen branch. This is shown from the value of tcount is greater than ttable value (3,397> 2,042), significance value 0,000 <0,05, and regression coefficient have positive value equal to 0,354, and (5) there is influence of organizational commitment to company performance at PT. Bina Artha Ventura Kebumen branch. This is shown from the tcount value is greater than the ttable value (3.605> 2.042), the significance value is 0.030 <0.05, and the regression coefficient has a positive value of 0.215.